1995
DOI: 10.1182/blood.v86.8.3173.bloodjournal8683173
|View full text |Cite
|
Sign up to set email alerts
|

The expression pattern of erythrocyte/megakaryocyte-related transcription factors GATA-1 and the stem cell leukemia gene correlates with hematopoietic differentiation and is associated with outcome of acute myeloid leukemia

Abstract: To understand the clinical implications of transcription factors and their biologic roles during cellular differentiation in the hematopoietic system, we examined the expression of GATA-1, GATA-2, and stem cell leukemia (SCL) gene in human leukemia cell lines and various leukemia patients using the reverse transcriptase-polymerase chain reaction. Cell lines exhibiting megakaryocytic or erythrocytic phenotypes had GATA-1, GATA-2, and SCL gene transcripts, while monocytic cell lines had no detectable GATA-1, GAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…Required for the growth, survival of erythroid precursors and mature cells [16], it also plays a fundamental role in megakaryocytic proliferation and differentiation [17]. Gata-1 expression was found in 43.9% of our patients confirming previous studies that showed expression of this factor in 50% AML [18][19][20], most often of the M6 and M7 FAB subtypes. As has been previously described, FAB M3 subtypes showed less Gata-1 expression than the other FAB subtypes grouped together (no M3) [20] (Fig.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Required for the growth, survival of erythroid precursors and mature cells [16], it also plays a fundamental role in megakaryocytic proliferation and differentiation [17]. Gata-1 expression was found in 43.9% of our patients confirming previous studies that showed expression of this factor in 50% AML [18][19][20], most often of the M6 and M7 FAB subtypes. As has been previously described, FAB M3 subtypes showed less Gata-1 expression than the other FAB subtypes grouped together (no M3) [20] (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…However, a very high expression of Gata1 was found in one of the two AML M7, none of them associated with Down syndrome. Overexpression Gata-1 in our series had a negative impact on EFS, underlying previous studies that found expression of this factor was related to a lower probability of achieving complete remission and survival [18][19][20]25].…”
Section: Discussionsupporting
confidence: 79%
“…Since we found GATA‐2 expression not in all but in 50% of the cHLs studied, it will be interesting to see if other GATA factors are expressed in GATA‐2‐negative cHLs, for example GATA‐3, which is aberrantly expressed in three of the four cHL‐derived cell lines 47, and if there is a link between the expression of GATA family members and the malignant phenotype of cHL, as has been described for acute myeloid leukaemia (AML) 52–54. In general, it may be possible that only a certain number of cHLs are associated with the expression of GATA factors.…”
Section: Discussionmentioning
confidence: 77%
“…The tissue-specific expression of GATA1 is mainly restricted to hematopoietic (erythroid cells, megakaryocytes, eosinophils and mast cells) and Sertoli cells (13,14). During normal hematopoiesis, GATA1 is not expressed in myeloid progenitor cells; however, previous studies have shown that leukocytes from AML patients express a significant amount of GATA1 (17)(18)(19). In addition, the overexpression of GATA1 has been shown to exert a negative effect on the event-free survival of AML patients (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…The tissue-specific expression of GATA1 is mainly restricted to hematopoietic and Sertoli cells (15,16). Previous studies have demonstrated that leukocytes from AML patients express a significant amount of GATA1 (17)(18)(19) and that the overexpression of GATA1 exerts a negative effect on the event-free survival of AML patients (20,21). These data led us to explore the possibility that GATA1 may directly upregulate DICER1 in AML.…”
Section: Analysis Of the Regulation Of Dicer1 Expression As Well As Tmentioning
confidence: 96%